TREATMENT OF ULCER GASTRODUODENAL BLEEDINGS: CURRENT STATE OF THE PROBLEM (A LITERATURE REVIEW) - O. N. Antonov; A. I. Cherepanin; M. S. Sineokaya (Неотложная медицинская помощь, 2016)
ABSTRACT. The problem of ulcer gastro-duodenal bleeding therapy is one of the most essential in urgent surgery. The bleeding is the most serious complication of peptic ulcer desease. It is observed in 15– 20% cases when patients have peptic ulcer diagnosis determined. In general the issues of bleeding therapy in gastroduodenal sphere are surveyed imperfectly. Some patulous endoscopic hemostasis methods don’t fully meet safety and confidence reqirements that preserves high level of general and post-operational lethality in our country and in the rest of the world.